Pemanfaatan Google App Script dalam Merancang Aplikasi Web Guna Meningkatkan Efisiensi Biaya Perusahaan - Tony Wijaya (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
Mobile applications trend are currently happening due to increased number of people holding smartphones. But this does not mean the end of web and desktop users. Mobile, web and desktop apps will always have its own market and users in manipulating data. The challenges for software developers are how to deliver software to all of those platforms as fast as possible. Efficiency is key in this research, that is to develop a hybrid app. Black box testing will be used in this research to make sure that efficiency is gained throughout the process compared to developing for each platforms independently. Through this research, hopefully can help software developers to develop and deliver applications for user efficiently in a short amount of time.